Apparel Production Optimization Model with Branch and Bound Method (Case Study: Sawargi Jersey Confectionery, West Java) - Athaya Alyanisa; Julita Nahar; Nursanti Anggriani (Research Collaboration Community (RCC), 2023)
The production optimization model can find optimal results and maximum profits from a production activity by considering certain limitations. In this research, a production optimization model was created based on data on apparel production in UMKM (Usaha Mikro, Kecil, dan Menengah) Konfeksi Sawargi Jersey in West Java by applying the Integer Linear Programming model and solving it using the Branch and Bound Method with the help of Software Python. This research was conducted because there are many business actors engaged in the same field, especially in the apparel and sports sectors, considering the problems that are often faced by UMKM owners, such as raw material supplies, production time, production costs, selling prices, production profits, and production limits, minimum and maximum production. Based on this study's results, the Branch and Bound Method application to optimize apparel production obtains more optimal results and maximum profits than the actual production carried out by UMKM Konfeksi Sawargi Jersey.